PEMANFAATAN KULIT GEMOR (Alseodaphne sp) SEBAGAI BAHAN UNTUK PEMBUATAN ANTI NYAMUK BAKAR The Possible Utilization of Gemor (Alseodaphne sp.) Bark as Material for the Manufacture of Anti Mosquito Agent - Zulnely, Zulnely; Martono, D. (Jurnal Ilmu dan Teknologi Kayu Tropis, 2003)
Gemor (Alseodaphne sp.) plants belong to the Lauraceae family and grow abundantly in particular Indonesian regions, predominantly South Kalimantan and Central Kalimantan.  It has been known that the bark portion of gemor plants can be used as an effective stuff or material to repel the mosquitoes (i.e. anti-mosquito agent).In this research, a laboratory-scale trial on the manufacture of anti-mosquito agent was conducted by diversifying its manufacturing formulations.  As such, two kinds of formulae were prepared.  The first formula (designated as A) consisted of the gemor bark (20 percent), which has been fragmented into flour, wood flour (60 percent), coconut-shell flour (10 percent), and wood flour of Cassiavera sp. (10 percent), and cassava flour (3 percent).  Meanwhile, the second formula (B) contained gemor bark flour (25 percent), wood flour (50 percent), coconut-shell flour (10 percent), Cassiavera wood flour (12 percent), and cassava flour (3 percent).  During the trial, in addition to varying or diversifying the formulation,  the manufacturing process (i.e. cooking) was also conducted in two different durations, i.e. 45- and 65-minutes.  Afterwards, the resulting anti-mosquito agents were tested of their efficacy through the burning process (i.e. the ease to get ignited, flaming duration, and efficacy to repel the mosquitoes).  Besides, assessing the qualities of the anti-mosquito agent was also conducted not through the burning process (i.e. the resistance of the agent to breakage, crumbling, and other destructive mechanical actions).The results revealed that the anti-mosquito agents manufactured using the two kinds of formulae (A and B) turned out to have almost similar characteristics, i.e. the ease to get ignited, flaming (burning) duration, and mosquito-repelling efficacy.  Meanwhile, the agent resulting from formula B disclosed better resistance to damage (crumbling/breakage) due to mechanical actions than the one from formula A. Formulation A and B are to use anti mosquito agent.